2021
DOI: 10.1093/mnras/stab1693
|View full text |Cite
|
Sign up to set email alerts
|

The general applicability of self-similar solutions for thermal disc winds

Abstract: Thermal disc winds occur in many contexts and may be particularly important to the secular evolution and dispersal of protoplanetary discs heated by high energy radiation from their central star. In this paper we generalise previous models of self-similar thermal winds - which have self-consistent morphology and variation of flow variables - to the case of launch from an elevated base and to non-isothermal conditions. These solutions are well-reproduced by hydrodynamic simulations, in which, as in the case of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Dust entrainment in photoevaporative extreme-ultraviolet-(EUV-) driven winds has first been investigated by Owen et al (2011), later by Hutchison et al (2016a,b), and very recently by Hutchison & Clarke (2021) and , building on the semi-analytical modelling of Clarke & Alexander (2016) (which has recently been generalised by Sellek et al 2021). All studies found an entrainment of dust grains of several µm in size.…”
Section: Introductionmentioning
confidence: 99%
“…Dust entrainment in photoevaporative extreme-ultraviolet-(EUV-) driven winds has first been investigated by Owen et al (2011), later by Hutchison et al (2016a,b), and very recently by Hutchison & Clarke (2021) and , building on the semi-analytical modelling of Clarke & Alexander (2016) (which has recently been generalised by Sellek et al 2021). All studies found an entrainment of dust grains of several µm in size.…”
Section: Introductionmentioning
confidence: 99%
“…Since we do not solve the hydrodynamics, we cannot determine the velocities 𝑣 for our simulations. However, we can assume that they are initially subsonic (Clarke & Alexander 2016;Sellek et al 2021) at the base of the wind and so the poloidal kinetic energy term 𝑣 2 𝑝 /2 is small compared to the thermal term 𝑃/𝜌, while the azimuthal kinetic energy term 𝑣 2 𝜙 /2 ∼ Φ 2 . Thus, we define the Bernoulli surface as the location where…”
Section: Example Temperature Structurementioning
confidence: 99%
“…Photoevaporative winds are thermally launched: they occur when the upper layers of a disc become heated by high energy ★ E-mail: ads79@cam.ac.uk radiation from either the central star (internal photoevaporation) or a massive neighbour (external photoevaporation) and the resulting pressure gradients drive material off of the disc. Broadly speaking, this is expected to happen for radii 𝑟 𝐺 𝑀 * 𝑐 2 𝑆 (for stellar mass 𝑀 * and sound speed in the wind 𝑐 𝑆 ) where the available thermal energy is enough to overcome the gravitational potential of the star (Shu et al 1993;Hollenbach et al 1994;Font et al 2004;Alexander et al 2014;Clarke & Alexander 2016;Sellek et al 2021). Equivalently, one can invert this to say that at a radius 𝑅, material must be heated above the escape temperature 𝑇 esc ∼ 𝐺 𝑀 * 𝜇𝑚 𝐻 2𝑘 𝐵 𝑅 (Owen et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Self-similar disk wind models explain that the power-law index of the base density profile limits an allowable range of v 2 in order for the streamline to reach infinity (Clarke & Alexander 2016;Sellek et al 2021). Self-similar thermal winds are known to generally take the maximum of the allowed M 2 at the base, otherwise, the whole R-z plane cannot be filled with the self-similar winds (Sellek et al 2021). In this way, the large-scale profiles of the disk winds also matter in determining the base property.…”
Section: Under These Conditions Equationsmentioning
confidence: 99%
“…One needs information on flow geometry to compute adiabatic cooling without performing hydrodynamic simulations. For disk photoevaporation, recent analytical models of thermally driven winds (Clarke & Alexander 2016;Sellek et al 2021) may be available for that purpose. Analytic modeling of c 2 (or flow structure) is a next step in future work.…”
Section: Input Parametersmentioning
confidence: 99%